10.61533 PENGARUH LEVERAGE, UKURAN PERUSAHAAN, DAN KOMISARIS INDEPENDEN TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN SUB SEKTOR PERDAGANGAN BESAR DAN ECERAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2019-2023 - Engelena, Sintia; Maharani, Yunita; Shinta Lestari, Deara (STIE IBEK Pangkalpinang, 2024)
This study aims to determine the effect of leverage, company size, and independent commissioners as independent variables on tax avoidance as the dependent variable. The object of this research is all wholesale and retail trade subsector companies listed on the Indonesia Stock Exchange in 2019-2023. The number of samples obtained was 17 companies using purposive sampling technique. This study uses secondary data in the form of financial statement data of wholesale and retail trade subsector companies listed on the Indonesia Stock Exchange. The data analysis technique uses multiple regression analysis methods processed with SPSS. The results showed (1) the leverage variable has no effect on tax avoidance with a significance value of 0.125 > from 0.05. (2) the firm size variable affects tax avoidance with a significance value of 0.003 < of 0.05. (3) the independent commissioner variable has no effect on tax avoidance with a significance value of 0.724 > from 0.05.